Steroid Avoidance in Liver Transplantation - José Oberholzer; Mohammed Al-Saghier; Norman M Kneteman (Canadian Journal of Gastroenterology)
Corticosteroids have always played a valuable role in transplantation. Unfortunately, they are subject to a wide range of side effects, such as hyperlipidemia, hypertension, diabetes mellitus, osteoporosis, growth retardation and Cushingoid appearance. Steroids may also exacerbate problems that existed before surgery, including malignancy, hepatitis B and hepatitis C. New, powerful immunosuppressants have allowed steroid use to be reduced or avoided altogether, but use of these regimens is not simple and may be associated with late acute rejection and recurrence of autoimmune disease. The present review examines the rationale for steroid avoidance in liver transplantation and assesses the new regimens that are currently being developed.